Urgensi Motivasi Dalam Meningkatkan Efektifitas Kelembagaan Perspektif Teoritik - Fathnun Tan (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
Employee work motivation is one of the determining factors in administering government and providing services to the community. Service that is dynamic and without favoritism, efficient and effective in terms of time, is the service that every community wants. And the quality of service really depends on the service provider, namely government officials. Apart from the factor of employee placement in accordance with their education and expertise so that the services provided can be effective and efficient, the work motivation factor of an employee is also very closely related to the quality of the service provided. Motivation is part of Human Resources Management in the context of coaching, developing and directing personnel. work in an organization. The source of work motivation, which is one of the determining factors in providing services by an employee, includes the opportunity to develop, the type of work carried out, and the feeling of pride in being part of the organization where they work. Apart from that, work motivation is also influenced by feelings of security at work, fair and competitive salaries, a pleasant work environment, appreciation for work performance and fair treatment from leaders.